Feasibility of Vegetable Residues Compost Used as the Growth Medium for Brassica chinensis L. Seedlings: Effects of Membrane Covering and Superphosphate Application - Jingjing Fu; Yunxiao Fang; Yongsheng Chen; Jie Cao; Aibing Wu; Zhenwei Wang (Agronomy, 2024)
In order to evaluate the feasibility of vegetable residues compost used as the growth medium for Brassica chinensis L. seedings, the effects of membrane covering and superphosphate application on the performance of tomato and mushroom residues aerobic compost were investigated. In the composting process, four treatments (T1: non-cover with non-addition, T2: membrane-covered with non-addition, T3: non-cover with superphosphate addition, and T4: membrane-covered with superphosphate addition) were explored. The results showed that membrane covering could effectively promote the degradation of lignocellulose, it had about 70% higher degradation rate than non-covered compost. The effect of superphosphate application was not significant. The humification indexes in Fourier Transform Infrared Spectroscopy (FTIR) and the fluorescence parameters were the main factors affecting the GI and chemical properties. The results manifested the membrane covering possess a higher conversion rate of humic substances, indicating better maturity. All the compost could almost meet the requirements of seedling substrate performance standards, especially the membrane-covered sample T2 had higher germination index (GI) value more than 100% and higher nutrient concentrations. Then, the four compost products were mixed with vermicompost, perlite, and vermiculite for the Brassica chinensis L. seedling raising experiment (T1B, T2B, T3B, T4B). It has been found that the compost-based substrate T2B with the best stability and maturity showed better seedling growth, and even comparable to peat substrate.